A global, empirical, harmonised dataset of soil organic carbon changes under perennial crops - Ledo, A.; Hillier, J.; Smith, P.; Aguilera, E.; Blagodatskiy, S.; Brearley, F.Q.; Datta, A.; Diaz-Pines, E.; Don, A.; Dondini, M.; Dunn, J.; Feliciano, D.M.; et al. (NATURE PUBLISHING GROUP, 2019)
A global, unified dataset on Soil Organic Carbon (SOC) changes under perennial crops has not existed till now. We present a global, harmonised database on SOC change resulting from perennial crop cultivation. It contains information about 1605 paired-comparison empirical values (some of which are aggregated data) from 180 different peer-reviewed studies, 709 sites, on 58 different perennial crop types, from 32 countries in temperate, tropical and boreal areas; including species used for food, bioenergy and bio-products. The database also contains information on climate, soil characteristics, management and topography. This is the first such global compilation and will act as a baseline for SOC changes in perennial crops. It will be key to supporting global modelling of land use and carbon cycle feedbacks, and supporting agricultural policy development.